Pelatihan Dasar Pertolongan Kecelakaan Penerbangan dan Pemadam Kebakaran - Oka, I Gusti Agung Ayu Mas; Anton Abdullah; Wildan Nugraha (Ilin Institute, 2021)
The purpose of the basic training for airport rescue and firefighting is to train participants to respond to emergencies that occur in the airport by providing rescue and firefighting services. The implementation method used is face-to-face training which consists of theory and practice. Participants in this training are citizens of Maldives who are employees of Maldives Airport Company Limited, and the stages of the training consist of preparation, implementation, and evaluation. The result of this training was that all of the participants passed the comprehensive exam so it can be concluded that the training has achieved the expected goals. The result of the training was analysed using questionnaires distributed to participants and through it was found that the training materials were very interesting and useful, as well as the instructors in general were very good, but there was one instructor who needed to improve his ability in English.